Favorite Arcellana stories - Arcellana, Francisco 1916-2002 (University of the Philippines Press, 2009)
Favorite Arcellana Stories is a centennial book of the University of the Philippines published among others in celebration of the institution's founding in 1908. It is a selection of some twenty-nine Arcellana short stories written and published over a period of nearly four decades. Many of these stories have seen several reprints in various anthologies and literature textbooks for Philippine schools, as well as translations from the original English into German, Italian, Russian, Korean (besides Tagalog) and published in their respective countries. A complete collection of the Arcellana body of work consisting of short stories, poems, essays, columns, and critiques is a daunting task, as many discrete pieces are scattered in public archives and private libraries not readily accessible if indeed still retrievable. The original manuscripts/typescripts have succumbed through the years to typhoons, floods, house movings, and even a Tondo fire. Happily, however, enough published material survived to perpetuate the memory of Francisco Arcellana as one of the best-loved and admired titans of Philippine letters."